2023
DOI: 10.3389/fcvm.2023.1182731
|View full text |Cite
|
Sign up to set email alerts
|

Association of gamma-tocopherol serum concentrations and blood pressure among adults in the United States: a cross-sectional study

Abstract: Backgroundhypertension is one of the major preventable risk factors for numerous diseases. The role of vitamin E in blood pressure (BP) has been controversial. We aimed to investigate the relationship between gamma-tocopherol serum concentration (GTSC) and BPMethodsData from 15,687 US adults from the National Health and Nutrition Examination Survey (NHANES) were analyzed. The correlations of GTSC with systolic BP (SBP), diastolic BP (DBP), and prevalence of hypertension were investigated by multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…The higher the concentration of GTSC, the higher the prevalence of hypertension and blood pressure. 46 This is similar to the results of Zhang et al 42 who found that when dietary vitamin E intake was greater than 40.53 mg/day, the risk of new hypertension was higher. The specific mechanism needs further study.…”
Section: Discussionsupporting
confidence: 89%
“…The higher the concentration of GTSC, the higher the prevalence of hypertension and blood pressure. 46 This is similar to the results of Zhang et al 42 who found that when dietary vitamin E intake was greater than 40.53 mg/day, the risk of new hypertension was higher. The specific mechanism needs further study.…”
Section: Discussionsupporting
confidence: 89%